Fibrosis in left atrial tissue of patients with atrial fibrillation with and without underlying mitral valve disease. Issue 4 (12th March 2004) - Boldt, A; Wetzel, U; Lauschke, J; Weigl, J; Gummert, J; Hindricks, G; Kottkamp, H; Dhein, S
Abstract : Objective: To examine the hypothesis that major extracellular matrix (ECM) proteins are expressed differently in the left atrial tissue of patients in sinus rhythm (SR), lone atrial fibrillation (AF), and AF with underlying mitral valve disease (MVD). Design: Case-control study. Patients: 118 patients with lone AF, MVD+AF, and SR. Main outcome measures: Collagen I, collagen III, and fibronectin protein expression measured by quantitative western blotting techniques and immunohistochemical methods. Results: Protein concentrations increased in patients with AF (all forms) compared with those in SR (all forms): collagen I (1.15 (0.11) v 0.45 (0.28), respectively; p = 0.002), collagen III (0.74 (0.05) v 0.46 (0.11); p = 0.002, and fibronectin (0.88 (0.06) v 0.62 (0.13); p = 0.08). Especially, collagen I was similarly enhanced in both lone AF (1.49 (0.15) and MVD+AF (1.53 (0.16) compared with SR (0.56 (0.28); both p = 0.01). Collagen III was not significantly increased in lone AF but was significantly increased in AF combined with MVD (0.84 (0.07) both compared with SR (0.46 (0.11); p = 0.01). The concentration of fibronectin was not significantly increased in lone AF and MVD+AF (both compared with SR). Furthermore, there was a similar degree of enhanced collagen expression in paroxysmal AF and chronic AF. Conclusions: AF is associated with fibrosis. Forms of AF differ from each other in collagen III expression. However, there was no systematic difference in ECM expression between paroxysmal AF and chronic AF. Enhanced concentrations of ECM proteins may have a role in structural remodelling and the pathogenesis of AF as a result of separation of the cells by fibrotic depositions.